2014
DOI: 10.1371/journal.pone.0098890
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Influenza Viruses in Waterfowl Used As Decoys in Andalusia, Spain

Abstract: A longitudinal study was carried out to determine the seroprevalence of avian influenza viruses (AIVs) in waterfowl used as decoys in Andalusia, southern Spain. A total of 2319 aquatic birds from 193 flocks were analyzed before and after the hunting season 2011–2012. In the first sampling, 403 out of 2319 (18.0%, CI95%: 15.8–19.0) decoys showed antibodies against AIVs by ELISA. The AI seroprevalence was significantly higher in geese (21.0%) than in ducks (11.7%) (P<0.001). Besides, the spatial distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…Influenza subtypes other than reported previously may have been circulating in the American mink populations from Northern Spain. In this sense, the few studies performed in order to describe the circulating AIV in wild birds from Spain reported a wide variety of low‐pathogenic AIVs and a wide range of prevalence of infection (Barral et al., ; Busquets et al., ; Pérez‐Ramírez et al., ; Jurado‐Tarifa et al., ; ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza subtypes other than reported previously may have been circulating in the American mink populations from Northern Spain. In this sense, the few studies performed in order to describe the circulating AIV in wild birds from Spain reported a wide variety of low‐pathogenic AIVs and a wide range of prevalence of infection (Barral et al., ; Busquets et al., ; Pérez‐Ramírez et al., ; Jurado‐Tarifa et al., ; ).…”
Section: Discussionmentioning
confidence: 99%
“…Influenza subtypes other than reported previously may have been circulating in the American mink populations from Northern Spain. In this sense, the few studies performed in order to describe the circulating AIV in wild birds from Spain reported a wide variety of low-pathogenic AIVs and a wide range of prevalence of infection (Barral et al, 2008;Busquets et al, 2010;P erez-Ram ırez et al, 2010;Jurado-Tarifa et al, 2014;). Continued interactions of mammals and birds increase the likelihood of IAV adaptation or reassortment, thereby allowing the emergence of novel influenza viruses in mammalian hosts and perhaps with zoonotic potential (Roberts et al, 2009;Britton et al, 2010;Sponseller et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Another surveillance program aimed at evaluating AIVs in waterfowl in Spain identified 1.1 and 0.3% of birds seropositive for H5 and H7. Of 47 samples that tested positive by both HI and ELISA, all tested negative by rRT-PCR ( Jurado-Tarifa et al, 2014 ). A study using both HI and RT-PCR to investigate ND in caged birds in Tehran, found that RT-PCR was more sensitive for detection of active carriers than was the HI test when 35 of 335 tested positive by RT-PCR but were not positive by HI ( Madadgar et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing MS or poultry categories is not possible due to large variations in the number of samples per country and per poultry category. LPAI has been detected in wild birds across the year and in several MS (Barral et al, 2008;Busquets et al, 2010;Perez-Ramirez et al, 2010Jurado-Tarifa et al, 2014;Latorre-Margalef et al, 2014;Swieton et al, 2017). Furthermore, the maps in Figure 1 show that some regions had seropositive holdings in 2014 and 2015.…”
Section: Morbiditymentioning
confidence: 99%
“…LPAI has been detected in wild birds across the year and in several MS (Barral et al., ; Busquets et al., ; Perez‐Ramirez et al., , ; Jurado‐Tarifa et al., ; Latorre‐Margalef et al., ; Swieton et al., ). Furthermore, the maps in Figure show that some regions had seropositive holdings in 2014 and 2015.…”
Section: Assessmentmentioning
confidence: 99%